2018
DOI: 10.1021/acsmedchemlett.8b00212
|View full text |Cite
|
Sign up to set email alerts
|

A Series of Indole-Thiazole Derivatives Act as GPER Agonists and Inhibit Breast Cancer Cell Growth

Abstract: The G protein-coupled estrogen receptor (GPER, GPR30) represents a promising target for the treatment of estrogen receptor α and β negative breast cancers. Previously reported agonists of GPER have shown that activation of GPER inhibits breast cancer cell proliferation. We report herein a new GPER agonist scaffold based upon in silico pharmacophore screening. Three of these compounds were found to increase cAMP at similar levels as the known GPER-selective agonist G-1. Compound was found to be selective for GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…These compounds were shown to bind exclusively to GPER1 without significant ESR1 binding above 100 mM ( Figure 2) (33). Previously, we identified a series of N-thiazol-2-yl-1H-indole-2-carboxamide derivatives as GPER1 agonists (30). These compounds exhibited a similar effect on breast cancer proliferation as reported in the literature in response to the GPER1-selective agonist, G-1 ( Figure 2 and demonstrated that MIBE blocks agonist activity at both GPER1 and ESR1 (36,37).…”
Section: Current Ligands For the Modulation Of Gper1 Signalingsupporting
confidence: 56%
See 1 more Smart Citation
“…These compounds were shown to bind exclusively to GPER1 without significant ESR1 binding above 100 mM ( Figure 2) (33). Previously, we identified a series of N-thiazol-2-yl-1H-indole-2-carboxamide derivatives as GPER1 agonists (30). These compounds exhibited a similar effect on breast cancer proliferation as reported in the literature in response to the GPER1-selective agonist, G-1 ( Figure 2 and demonstrated that MIBE blocks agonist activity at both GPER1 and ESR1 (36,37).…”
Section: Current Ligands For the Modulation Of Gper1 Signalingsupporting
confidence: 56%
“…The reduction of binding and ERE activation was accomplished with the addition of an isopropyl group to the scaffold to make G-36 (29). While the G-series has become the standard for GPER1 agonists and antagonists, the success with the compounds has been variable and may be related to the tissue-specific signaling events of GPER1 (30,31).…”
Section: Current Ligands For the Modulation Of Gper1 Signalingmentioning
confidence: 99%
“…On the basis of affinity or efficacy as transcriptional activators, some ligands have been revealed to discriminate between GPR30 and ER subtypes. (14)(15)(16)(17) Subsequently, a considerable effort has been focused on the development of receptor-selective agonists and antagonists for GPR30, ERα, or ERβ. A compound, G-1, has been found to be a cell-permeable, nonsteroidal, dihydroquinoline, high-affinity, selective agonist for GPR30, and it displays no activity on ERα or ERβ at concentrations up to 10 μM.…”
mentioning
confidence: 99%
“…Previously, our group explored binding interactions in a series of indole-thiazole derivatives that exhibited agonism at GPER (42). Molecular homology modeling found that the indole-thiazole derivatives exhibited -stacking similar to G-1 of the aromatic groups with F206 45.49 and F208 45.51 within the binding pocket of GPER (33,34,42). These results suggested that the tetrahydroquinoline is not required for GPER activity.…”
Section: Discussionmentioning
confidence: 99%